THE ROLE OF FOLK MUSIC IN THE EDUCATION OF AESTHETIC MUSIC IN FUTURE MUSIC EDUCATION TEACHERS (Archive of Conferences, 2022)
Music pedagogy plays an important role in educating people artistically and aesthetically. Among them, traditional folk music has the ability to quickly affect a person, is easily accepted and form a person's aesthetic attitude to the outside world. The article reflects the love for national music and values. Instead of folk music, special attention is paid